Correspondence (transcripts), - Parker, Samuel, 1779-1866
Transcripts of letters to and from Samuel Parker. One letter is from Samuel Parker from Lexington, Missouri, to his family on his journey in April 1835. The second letter, addressed to his wife is sent from St. Louis in August of 1835. He describes meeting the Flatheads, the Nez Perce, and the Spokane Indians. The third letter is by Narcissa Whitman addressed to dear brothers and sisters and was sent in July 1836 from "beyond the Rocky Mountains." Narcissa Whitman talks about her future home and the journey. The final letter is sent from Jane Prentiss to Mrs. Samuel Parker, dated September 1838 and talks about the Whitmans and the Spaldings. This letter says "copy of a letter owned by Mr. Alexander Mack of New York," but it is not known when it was transcribed. There is no indication of the location of the original copies of the other letters.